Concomitant administration of meningococcal vaccines with other vaccines in adolescents and adults: a review of available evidence. Issue 9 (2nd September 2019) - Alderfer, Justine; Srivastava, Amit; Isturiz, Raul; Burman, Cynthia; Absalon, Judith; Beeslaar, Johannes; Perez, John
ABSTRACT: Invasive meningococcal disease (IMD), a rapidly progressing and potentially fatal illness, disproportionately affects adolescents and young adults. While IMD is best prevented by vaccination, vaccine uptake in these groups is low. An evidence-based understanding of the safety and effectiveness of concomitant vaccination of meningococcal vaccines, including the newer MenB protein vaccines and the more established MenACWY conjugate vaccines, with other vaccines recommended for adolescents and young adults may help maximize vaccination opportunities. We identified 21 studies assessing concomitant administration of meningococcal vaccines with other vaccines in adolescents and adults. Although studies varied in methodology, concomitant administration generally did not affect immunogenicity of the meningococcal or coadministered vaccines. In some cases, reactogenicity increased following concomitant administration, but no definitive safety concerns were raised. In general, data suggest that meningococcal vaccines can be safely and effectively coadministered with other vaccines.